Experimental Investigation of Underwater Optical Wireless Communication for Correlated SIMO Channel Under Temperature-Induced Turbulence - Weijie Liu; Wenli Jiang; Nuo Huang; Zhengyuan Xu (IEEE Photonics Journal)
Turbulence is an intractable issue for underwater optical wireless communication (UOWC). In this paper, the effects of temperature-induced turbulence on the UOWC system with correlated single-input multiple-output (SIMO) channel are comprehensively investigated, and the feasibility of employing a detector array in mitigating the turbulence-induced signal fluctuation is experimentally verified. Experimental results show that the spatial diversity can ensure the satisfactory bit error rate (BER) and outage probability performance with the maximum ratio combining (MRC) under correlated turbulence channel. The optimal paired combinations can achieve a signal-to-noise ratio (SNR) gain above $\text{3 dB}$ over the single branch receiver at the BER of $10^{-3}$ . Moreover, the diversity gain will be reduced by the subchannel correlation when the arrayed receiver elements adopted to mitigate the turbulence effect fail to be placed sufficiently far apart.